If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 = t + 4t Combine like terms: t + 4t = 5t 39 = 5t Solving 39 = 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 39 + -5t = 5t + -5t Combine like terms: 5t + -5t = 0 39 + -5t = 0 Add '-39' to each side of the equation. 39 + -39 + -5t = 0 + -39 Combine like terms: 39 + -39 = 0 0 + -5t = 0 + -39 -5t = 0 + -39 Combine like terms: 0 + -39 = -39 -5t = -39 Divide each side by '-5'. t = 7.8 Simplifying t = 7.8
| (X-3)(x+4)=-4(4+x) | | 17x+56=23x+38 | | -7-35x-40=11 | | 3l^2-12l-960=0 | | 4x-5-8x=-8 | | x^2-4.36*x=0 | | 8(2x-6)=34 | | 5-(3-P)=7p | | 5-(3-P)=7 | | 6x-2(3x+4)=-20 | | 20p+250=500 | | 3b+38=125 | | -8-32x+8=6 | | 2(x-1)=58 | | 4+19y-2=6y+122-2y | | -8-4(-8x-2)=6 | | 21k^2+91k+98=0 | | .05+.10(2n)=4.20 | | x^4-3x^2+30=0 | | 0=8x^2+6x+3 | | -24x-8-4x=-5 | | 10x^4-x^2-9=0 | | -4x-10k= | | 3(x+2.94)=2x | | 75x^2=3 | | 2m+7-2m+6=x | | 5x+9.16=3x+12 | | 12(3x+6)-7(2x-4)=4x-20 | | 15x-35=8 | | 5x+7=12x-56 | | 32=5x-3 | | -x^4=25-26x^2 |